SnS thin films prepared by encapsulated sulfurization - Sakrani, Samsudi (Persatuan Sains & Teknologi Keadaan Pepejal Malaysia, 1996)
Tin sulphide (SnS) thin films were grown using a method called encapsulated sulfurization from the Sn/S stacked layers previously coated on a glass substrate at pressure 10-5 mbar and film thickness ratios; Sn: S= 1:1, 1:2, 1:3. In this technique the samples were placed in a carbon block and annealed in argon gas at temperatures between 260-450 oC for three hours to allow the formation of SnS thin films by chemical reaction which took place in the Sn/S bilayer. In the early stage (260 oC) Sn was sulfurized between 300-400 oC changed the process rapidly and dominantly into SnS with improved crystallinity. The measured resistivities were found to be between 0.65-2.92 Sm-1 over the range of substrate temperature concerned.